Anemia in the first trimester is associated with anemia during pregnancy in Sidotopo Wetan Community Health Center, Surabaya - Putri Ancila Citra Prasetya; Baksono Winardi; Djohar Nuswantoro (Universitas Airlangga, 2020)
Objective: To analyze association between anemia in the first trimester and preeclampsia during pregnancy in Sidotopo Wetan Community Health Center Surabaya.Materials and Methods: This study was a analytic case control study. The samples were 49 women with preeclampsia as case group and 49 women non-preeclampsia as control group. The data were secondary data collected from medical record of pregnancy women on Sidotopo Wetan Community Health Center Surabaya from January 2016 – Desember 2017. The analysis was done by Chi Square Statistics.Results: 79,6% women in preeclampsia group and 93.9% women in non-preeclampsia group was not anemia in the first trimester. There is association between anemia in the first trimester and preeclampsia during pregnancy in Sidotopo Wetan Community Health Center Surabaya (p = 0.037; OR = 3.932 (CI 95% = 1.010 – 15.303)).Conclusion: There is association between anemia in the first trimester and preeclampsia during preg-nancy in Sidotopo Wetan Community Health Center Surabaya.